The Priorities of Iranian Male Adolescents Health Needs - Elham Zare PhD (American Journal of Men's Health, 2017)
Health in the adolescence period guarantees the next generation’s health. The assessment of health needs is the first stage for the implementation of health promotion interventions. This study aimed to assess the priorities of male adolescent’s health needs in Tehran, Iran, in year 2015. This cross-sectional correlational study was conducted with 1,200 male adolescents aged between 13 and 18 years. Single male adolescents studying in public guidance and high schools in Tehran, Iran, in year 2015 were chosen using a random multistage sampling method. Data were collected using the male adolescent health need assessment scale. The data were analyzed using descriptive and inferential statistics. It was found that while the lowest score was for the domain of sexual health, other domains had average or higher than average scores. More attention should be paid to the sexual health needs of male adolescents. Policy makers need to design strategies that help meet the health needs of male adolescents.